Comparative analysis of injury and illness rates among team USA athletes at the Tokyo 2020 Summer Olympic and Paralympic Games - Post, E. G.; Cali, M. G.; Clark, S. C.; Noble-Taylor, K. E.; Robinson, D. M.; Hasley, I. B.; Larson, E. G.; McPherson, A. L.; Anderson, T.; Finnoff, J. T.; Adams, W. M. (Orthopaedic Journal of Sports Medicine, 2024)
Background: Previous research has reported higher rates of both injury and illness among Paralympic athletes compared with Olympic athletes during the Winter Olympic and Paralympic Games, but no studies have directly compared injury and illness incidence between Olympic and Paralympic athletes competing in a Summer Games.